2007
DOI: 10.1126/science.1136598
|View full text |Cite
|
Sign up to set email alerts
|

Single Photon-Induced Symmetry Breaking of H 2 Dissociation

Abstract: H 2 , the smallest and most abundant molecule in the universe, has a perfectly symmetric ground state. What does it take to break this symmetry? Here we show that the inversion symmetry can be broken by absorption of a linearly polarized photon, which itself has inversion symmetry.In particular, the emission of a photoelectron with subsequent dissociation of the remaining H + 2 fragment shows no symmetry with respect to the ionic H + and neutral H atomic fragments. This result is the consequence of the entangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 22 publications
5
163
0
2
Order By: Relevance
“…In excellent agreement with the ab initio calculations and previous measurements for one photon single ionization [111] all relevant fragmentation pathways, like ground-state dissociation (maximum at E KER = 0), dissociation via the 2pπ u channel (E KER ≈ 9 eV) as well as contributions and interferences involving the decay of doubly excited (Q2) states [109] are well resolved (Fig. 9a), providing a sound basis for the understanding of TPDI.…”
Section: Direct and Sequential Tpdi Of Dsupporting
confidence: 85%
“…In excellent agreement with the ab initio calculations and previous measurements for one photon single ionization [111] all relevant fragmentation pathways, like ground-state dissociation (maximum at E KER = 0), dissociation via the 2pπ u channel (E KER ≈ 9 eV) as well as contributions and interferences involving the decay of doubly excited (Q2) states [109] are well resolved (Fig. 9a), providing a sound basis for the understanding of TPDI.…”
Section: Direct and Sequential Tpdi Of Dsupporting
confidence: 85%
“…Because in molecules the excess photon energy can be distributed among internal nuclear and electron degrees of freedom however, the situation is much more complex than in atoms, and a clearcut proof of the interference effects is missing. In a very recent work [11], it has been clearly demonstrated that such interference effects cause symmetry breaking in dissociative photoionization. A first observation of asymmetric photoelectron emission from H 2 has been reported in pioneering experiments by Lafosse et al [81].…”
Section: Photoionization Of H 2 Through Autoionizing Statesmentioning
confidence: 99%
“…Thus regions I and II cannot be the result of a single-step direct photoionization. They are the fingerprint of a delayed emission of an Auger electron from H 2 doubly excited states (either Q 1 or Q 2 [11]). These states can either dissociate due to the repulsive character of the corresponding potential energy curve or decay by autoionization into the 2pσ u or 1sσ g states when such a decay is faster than the time required for an effective dissociation.…”
Section: Photoionization Of H 2 Through Autoionizing Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise that TISE, accurate solutions of the TDSE are rare and available only for very simple cases. 40 A time-dependent study of an atom interacting with a surface seems to be a natural continuation of the TM clusters on Gr problem. However, this problem has to overcome two conceptual physical challenges.…”
Section: Introductionmentioning
confidence: 99%